2015
DOI: 10.1097/pas.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tumor Deposits on Colonic Adenocarcinoma AJCC TNM Staging and Outcome

Abstract: The definition of tumor deposits (TD) in colonic adenocarcinoma has been modified in different editions of AJCC/TNM staging system. Studies have shown that the presence of TD is associated with advanced tumor growth and poor prognosis. Most of these data were obtained in patients with simultaneous lymph node (LN) metastases. Reports focusing on the impact of TD in patients without LN metastasis are limited. We retrospectively restaged all right-sided colonic adenocarcinoma over a 10-year period using criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 19 publications
7
65
0
Order By: Relevance
“…examined right‐sided colonic adenocarcinomas only, showing significantly worse survival in N1c patients than N0 patients. This is comparable to the significantly worse DFS noted in colonic tumours in our study . Belt et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…examined right‐sided colonic adenocarcinomas only, showing significantly worse survival in N1c patients than N0 patients. This is comparable to the significantly worse DFS noted in colonic tumours in our study . Belt et al .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Jin et al examined right-sided colonic adenocarcinomas only, showing significantly worse survival in N1c patients than N0 patients. This is comparable to the significantly worse DFS noted in colonic tumours in our study [24]. Belt et al found more recurrences in TD-positive patients than TD-negative patients (65.1% vs 39.1%, respectively) [25].…”
Section: Discussionsupporting
confidence: 90%
“…We therefore speculate that TD may be associated with a risk of all‐cause death or cancer‐specific death at least similar to a positive lymph node in all N categories. This speculation is supported by a study on N0 cases, but not by others . In addition, TD is prognostically more important in CRC of lower N categories, as shown by the trend of higher TD‐associated HR in CRC of lower N categories.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies demonstrated that patients with stage II but with TD behave similarly to stage III, but the evidence supporting this change are retrospective studies that classified TD as lymph node metastasis or based the TD definition on diameter . When a comparison between stage II cases with TD and cases with stage III (with lymph node metastasis) has been performed, there are no differences in survival …”
Section: Discussionmentioning
confidence: 99%